دور البيئة التشريعية في تطبيق معايير الحلال في المنتجات والخدمات وملائمة النظام القانوني الليبي استرشاداً بالمعايير الماليزية = Legal environment role on the application of Halal product and serves standards and The suitability of Libyan legal in light of Malaysian standards - Laeba, Muhammad; Ahmed, Ahmed Salem (Faculty of Syariah and Law at Universiti Sains Islam Malaysia (USIM), 2018)
تستند معايير الحلال إلى مضامين دينية تنفرد بها عن غيرها من النظم القانونية ،ولذلك فإن البيئة التشريعية المحيطة توثر بشكلٍ مباشر على تطبيق هذه المعايير ،بحيث تزداد تلك الآثار تعقيداً كلما تضمنت البيئة مضامين تتعارض مع المضامين الشرعية للحلال ،وأخداً في الإعتبار أهمية قطاع الحلال من الجوانب الدينية والإستثمارية ،حاول الباحث تسليط الضوء على أثر البيئة التشريعية في المساهمة في تقنين الحلال وتبني معايير الحلال في جانبي المنتجات والخدمات لمحاولة توظيف النظم القانونية القائمة في الدول التي لم تتبنى معايير الحلال في تبني هذه المعايير من خلال المقاربة بينهما ،وقد استشهد الباحثان في ذلك بالنظام القانوني الليبي لكونه من ضمن الأنظمة التي لم تهتم بتقنين الحلال ،وبعد تحليل القوانين ذات الصلة بالحلال في جانب المنتجات والخدمات تبين أن البيئة التشريعية الليبية غنية بالمضامين التي تُحاول معايير الحلال تقنينيها ،حيث أنها وإن لم تُقنن الحلال بمفهومه المعاصر ،لاسيما كما جاء في المعايير الماليزية التي أتخدها الباحثان كمعيار للمقاربة ،إلا أنه بشكل ضمني يتضمن معظم مضامين هذه المعايير ،مما أوصى معه الباحثان بتبني معايير الحلال للإستفادة من هذا القطاع الرائد في ليبيا ،كما أوصا بإعتبار منهج التحليل المُسبق للبيئة التشريعية المحلية قبل تبني معايير الحلال لخلق الظروف المناسبة لتطبيقها. ********************************************************** Halal standards are based on religious values that are unique to other legal systems. Consequently, the legislation of the surrounding environment may have direct effects on the application of these standards, and that these effects become more complex the more the environment embodied in the contents clash with the Shariah-based Halal. In order to show the importance of the Halal sector in both religious and investment aspects, this paper examined the contribution of the legislative environment to Halalization, and how Halal standards could be adopted in the products and services by the existing legal systems of the countries that have not adopted them, through comparison between legal systems. The paper used the Libyan legal system as a case study because its system is less concerned about Halalization. After analyzing the laws related to Halal products and services, it was found that the Libyan legislative environment is rich with the contents of Halalization; even if the Halalization is not codified in the contemporary concept just as stated in the Malaysian standards that the paper adopts as a criterion for the comparison, it implicitly includes most of the contents of these standards. The paper recommends that the Libyan system should adopt the Halal standards to benefit from this sector.